2023
DOI: 10.3389/fvets.2022.1005102
|View full text |Cite
|
Sign up to set email alerts
|

Which animal-to-feeding-place ratio at time-controlled hay racks is animal appropriate? Preliminary analysis of stress responses of horses

Abstract: IntroductionAutomated feeding systems offer numerous advantages for animals and humans, but the associated benefits and risks can often only be seen under practical conditions. The space allowance (~80 cm per horse) at time-controlled hay racks for horses in group housing, unlike at partitioned feeding stands or transponder-controlled feed stations, currently falls below the required individual distance between the horses, which can result in a high level of aggression between the horses due to the lack of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, it has been reported that associating the measurement results made in this way directly with the welfare of the horse may lead to false results and it is necessary to carefully evaluate whether an abnormal result is due to an acute or chronic condition (Lesimple 2020). Otherwise, there are studies that correlate welfare with the evaluation of the environmental conditions of the horses, such as housing and management (Ruet et al, 2019;Rosselot et al, 2019;Kelemen et al, 2021;Mazzola et al, 2021;Mactaggart et al, 2021;Gehlen et al, 2021;de Oliveira and Aurich, 2021;Baumgartner et al, 2023). Bibliometry also known as bibliometrics is a quantitative method to analyze and measure different features in scientific literature and papers.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that associating the measurement results made in this way directly with the welfare of the horse may lead to false results and it is necessary to carefully evaluate whether an abnormal result is due to an acute or chronic condition (Lesimple 2020). Otherwise, there are studies that correlate welfare with the evaluation of the environmental conditions of the horses, such as housing and management (Ruet et al, 2019;Rosselot et al, 2019;Kelemen et al, 2021;Mazzola et al, 2021;Mactaggart et al, 2021;Gehlen et al, 2021;de Oliveira and Aurich, 2021;Baumgartner et al, 2023). Bibliometry also known as bibliometrics is a quantitative method to analyze and measure different features in scientific literature and papers.…”
Section: Introductionmentioning
confidence: 99%